2021
DOI: 10.1111/ajo.13416
|View full text |Cite
|
Sign up to set email alerts
|

A cannulated prolactin series reduces the need for further investigations in women with infertility and lowers the number of false positive screening prolactin measurements

Abstract: Background:The prevalence of hyperprolactinaemia in women presenting for infertility investigation has been found to be up to 17%, and many of these women are asymptomatic. Prolactin levels may be elevated by stress, including phlebotomy and not be of clinical significance. A cannulated prolactin study may be a useful way to discriminate this. Aim:To determine the utility of a cannulated prolactin series in women presenting with infertility who have a raised prolactin measurement at referral for first fertilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…5 Other studies investigating serial sampling over 120 min include a study of 42 (88% female) patients where random (nonrested) prolactin was elevated on more than one occasion, in which normalisation occurred in 12 cases (29%), 6 and a study of 44 women specifically referred for fertility assessment, in which normalisation occurred in 27 cases (61%). 7 The latter study specifically commented that all patients with a normal prolactin at any time during serial sampling had a normal prolactin at the end of serial sampling, consistent with our finding that a single rested sample is equally effective as serial sampling. Macroprolactin interference and use of medications associated with hyperprolactinaemia were systematically excluded in all three studies.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…5 Other studies investigating serial sampling over 120 min include a study of 42 (88% female) patients where random (nonrested) prolactin was elevated on more than one occasion, in which normalisation occurred in 12 cases (29%), 6 and a study of 44 women specifically referred for fertility assessment, in which normalisation occurred in 27 cases (61%). 7 The latter study specifically commented that all patients with a normal prolactin at any time during serial sampling had a normal prolactin at the end of serial sampling, consistent with our finding that a single rested sample is equally effective as serial sampling. Macroprolactin interference and use of medications associated with hyperprolactinaemia were systematically excluded in all three studies.…”
Section: Discussionsupporting
confidence: 85%
“…A study of 235 (92% female) patients undergoing serial prolactin sampling identified normalisation of the initial prolactin in 41 cases (17%) and normalisation on repeat sampling in 23 of the remaining 194 cases (12%), with repeat sampling obtained after 120 min 5 . Other studies investigating serial sampling over 120 min include a study of 42 (88% female) patients where random (nonrested) prolactin was elevated on more than one occasion, in which normalisation occurred in 12 cases (29%), 6 and a study of 44 women specifically referred for fertility assessment, in which normalisation occurred in 27 cases (61%) 7 . The latter study specifically commented that all patients with a normal prolactin at any time during serial sampling had a normal prolactin at the end of serial sampling, consistent with our finding that a single rested sample is equally effective as serial sampling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tsur et al [13] found that it PRL returned to normal at 60 min in 86 patients (24%) and at 90 min in 87 patients (24.2%); thus, prolonging the test period did not signi cantly contribute to the diagnostic process. Meanwhile, previous studies have stated that stress-related PRL elevation stems from a fear of blood drawing [7,14]. However, the stress-related PRL elevation results in previous studies were similar to that of the present study, which examined blood samples taken using the venous puncture method, suggesting that PRL elevation may be independent of a fear of venous puncture.…”
Section: Discussionsupporting
confidence: 84%